"La lagartija de la panza blanca" de Yolanda Oreamuno: una lectura desde la voz narrativa - Caamaño, Virginia (2008)
This article establishes a dialogue between Yolanda Oreamuno´s short story and three of her essays in order to point out the coherence of the costarrican author´s ethic and aesthetic vision.